Taxonomy of Tele-Technology - Beattie, Earle (Canadian Journal of Communication, 1979)
ANALOG (Analogue) SIGNALS, SYSTEMS: Non-digital high information - rate services, offering the most efficient use of the spectrum, but not having the advantage of digital systems in versatility. Telephone circuits, cable-TV, television and radio are systems using the analog code. There is a continuous flow of signals in a form analogous to what goes in at one end and comes out at the other. Analog signals can be transformed into digital signals by Pulse Code Modulation.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjIyMzAvY2pjLjE5Nzl2Nm4xYTIyOA